2000
DOI: 10.1097/00000539-200010000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Postdural Puncture Headache: A Randomized Comparison of Five Spinal Needles in Obstetric Patients

Abstract: This prospective, blinded, randomized study compares the incidence of postdural puncture headache (PDPH) and the epidural blood patch (EBP) rate for five spinal needles when used in obstetric patients. One thousand two women undergoing elective cesarean delivery under spinal anesthesia were recruited. We used two cutting needles: 26-gauge Atraucan and 25-gauge Quincke, and three pencil-point needles: 24-gauge Gertie Marx (GM), 24-gauge Sprotte, and 25-gauge Whitacre. The needle for each weekday was chosen rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
2
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 6 publications
4
107
2
5
Order By: Relevance
“…Thirty-nine studies (16 RCT, [10][11][12]14,[16][17][18][19][20][21]23,24,26,[28][29][30] ten cohort studies, [33][34][35][36][38][39][40][41][42][43] and 13 case series 45,[47][48][49][50][51][53][54][55][56][57][58][59][60] ) contained data on frequency of ADP or PDPH (Table I). Figures 1 to 3 summarize the meta-analyses of ADP and PDPH risks for different epidural and spinal needles.…”
Section: Dp and Pdph Ratesmentioning
confidence: 99%
“…Thirty-nine studies (16 RCT, [10][11][12]14,[16][17][18][19][20][21]23,24,26,[28][29][30] ten cohort studies, [33][34][35][36][38][39][40][41][42][43] and 13 case series 45,[47][48][49][50][51][53][54][55][56][57][58][59][60] ) contained data on frequency of ADP or PDPH (Table I). Figures 1 to 3 summarize the meta-analyses of ADP and PDPH risks for different epidural and spinal needles.…”
Section: Dp and Pdph Ratesmentioning
confidence: 99%
“…[11] There are many studies proving that blunt-tipped needles reduce the incidence of headache. [12][13][14][15] Westbrook et al [15] and Ready et al, [13] in their distinct studies with blunt-and sharp needles having the same outer diameter, found that CSF loss was less with blunt needles. Katı et al, [16,17] in a study with 60 patients, did not find any statistically significant difference between blunt and sharp needles with regard to headache.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies with spinal anesthesia practices comparing the blunt needles and sharp needles with smaller diameter, it was reported that blunt needles were less likely to cause to headache. [13][14][15] Vascular penetration during invasive processes is a risk factor that may happen in all injection procedures. Potential complications of this situation are bleeding, hematoma formation, and intravascular drug injection.…”
Section: Discussionmentioning
confidence: 99%
“…6 The Sprotte spinal needle (Pajunk GMBH, Geisingen, Germany) has been associated with a low incidence of PDPH in parturients. [7][8][9][10][11] The Special Sprotte™ epidural needle is a modification of the non-cutting Sprotte spinal needle. It has a solid bullet-shaped tip with a lateral opening for passage of an epidural catheter.…”
Section: Discussionmentioning
confidence: 99%